2008
DOI: 10.1097/iop.0b013e318182aff7
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Intraorbital Abscesses and Cavernous Sinus Thromboses Secondary to Streptococcus milleri With a Favorable Outcome

Abstract: A 51-year-old woman with left proptosis, diplopia, headache, and nausea was found to have bilateral intraorbital abscesses, left superior ophthalmic vein thrombosis, bilateral cavernous sinus thromboses, and a left temporal lobe intracerebral abscess. Because the paranasal sinuses were unaffected, a dental origin was suspected and confirmed. The causative organism was Streptococcus milleri. Aggressive surgical intervention included bilateral orbital abscess drainage and dental extraction, and medical therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Staphylococcus aureus is the causative agent in more than half of septic CST cases,4 , 12 , 13 most of which arise from sphenoidal and ethmoidal sinus infections 10 , 13. Mixed organisms are usually found in odontogenic sources and these include streptococci (notably of the β haemolytic variety) and anaerobes 8 , 14. Early addition of meropenem and clindamycin was therapeutic for the initial infective focus and CST, and also the septic pulmonary deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus is the causative agent in more than half of septic CST cases,4 , 12 , 13 most of which arise from sphenoidal and ethmoidal sinus infections 10 , 13. Mixed organisms are usually found in odontogenic sources and these include streptococci (notably of the β haemolytic variety) and anaerobes 8 , 14. Early addition of meropenem and clindamycin was therapeutic for the initial infective focus and CST, and also the septic pulmonary deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Other reported complications of disseminating dental infections include brain abscess (21)(22)(23)(24), septicemia in a patient with multiple myeloma (25), deep neck infection (26,27), mediastinitis (14,(28)(29)(30), necrotizing fasciitis (31)(32)(33), orbital abscess (34)(35)(36), and cervical spondylodiscitis with spinal epidural abscess (37). It has been suggested that some host-related factors may contribute toward increased morbidity and mortality associated with acute dental abscesses, including diabetes, chronic alcohol and tobacco consumption, malnourishment, and the use of illicit substances (26,27,33).…”
Section: Complications Stemming From Acute Apical Abscessesmentioning
confidence: 99%
“…They occur in 1% of orbital and periorbital complications of sinusitis 6. Bilateral intraorbital abscesses are extremely rare, and cases reported are usually associated with virulent pathogens and more serious complications 5,7…”
Section: Discussionmentioning
confidence: 99%
“…Inability to culture organisms is attributed to preceding antibiotic therapy 1,9. The most common pathogen in cases with intracranial complications is Streptococcus milleri 7,8,111.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation